Marketing strategy analysis and formulation for Jatinangor City Park to regain competitiveness in Jatinangor property industry - Sebastian Pratama Sakti (Priviet Social Sciences Journal, 2026)
This study develops a competitive marketing strategy for Janati Park (Jatinangor City Park) in the Jatinangor residential market, where sales underperform despite strong access to universities and key corridors in the area. Guided by the 4C diamond, the analysis combines PESTEL and Porter’s Five Forces with VRIO and positioning differentiation brand (PDB) diagnostics, and synthesizes priorities through weighted SWOT and a TOWS matrix. Data were triangulated via semi-structured interviews with management and customers, participant observation of Janati Park and direct competitors, and secondary sources for industry and regulatory contexts. The results show that location and a large land bank are durable strengths, whereas weak amenity depth, visible maintenance deficits, and inconsistent branding erode trust and make premium pricing difficult to justify. Customer journeys confirm that location is the most decisive attribute, but conversion leaks to competitors when buyers prioritize lower entry prices and lifestyle facilities aligned with student end-users. The recommended strategy retains the project’s strategic location positioning while adding a student-centered “integrated activity and investment zone” identity, completing promised amenities, improving cleanliness and drainage reliability, expanding student-oriented services and event partnerships, and institutionalizing “peace of mind” through governance and service standards. These actions translate land scale into everyday value and restore the credibility needed for sustainable competition.